The Impact of Primatani Program in Accelerating Transfer of Agricultural Technology for Farmers and Local Government - Dian Adi Anggraeni Elisabeth, Mrs. (FIA UB, 2012)
This study aims to obtain the information about the impact of Primatani program in accelerating transfer of agricultural technology. Generally, farmers who assisted in Primatani could experience the impact of technology introduction although they did not get intense assistance from Bali AIAT. By the formation of working groups within the farmer group could improve the efficiency, especially in terms of providing farming inputs. Unfortunately, the impact cannot be really experienced by non-targeted farmers although they have ever heard about technologies introduced. For local government, the adoption of technology and concept of Primatani supported Bali Provincial Government in realizing their vision âBali Mandaraâ named Integrated Farming System (Simantri). Replication of Primatani concept in a massive level has been carried out by local government since 2009 at various villages. For field extension agents, the impact of Primatani could be felt by the utilization of introduced technologies as a program material.